Voorbeeldmateriaal in woordeboeke - Lombard, F.J. (Lexikos, 1992)
Usage Examples in DictionariesUsage examples can include citations, verbal illustrations and / or collocations and should contribute semantically, syntactically and pragmatically towards the way lemmas are presented in a given descriptive dictionary. To be as functional as possible, usage examples should meet certain criteria: they should represent real language and not a stylistic variant of language, they should meet the needs of the target-users of the dictionary, they must be easily understood and they should not be contentious. Citations may have certain deficiencies, but the benefits of a good syntactic component far outweigh these. Usage examples can successfully be employed in standard dictionaries, although their treatment in Afrikaans dictionaries leaves something to be desired.